Field notes contributed by Kathy Bayer, November 11, 1988 - Bayer, Kathyet al (1988)
List of birds and locations contributed by Kathy Bayer. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1988. Epson - sheet feed/flatbed